Prototipe Perpustakaan Virtual Museum & Galeri Sby*Ani Dengan Design Innovation Methode - Amalina, Nabila; Susetyarto, Martinus Bambang (Konsorsium Cendekiawan Indonesia, 2022)
Virtual architecture has unlimited space. The space is one of the answers to the fulfillment of space needs on limited land in the real world. The development of the library at the SBY*Ani Museum and Gallery is actually thinking about using virtual architecture to meet the demands of providing an alternative space that can functionate the library to keep books and collections, with low cost and sustain quality layout management, and flexible visiting times for readers/borrowers. Purpose of the research was finding a library prototype that give a pleasant space experience and user friendly, also having an impact on the sustainability of library management which was combaining architecture of the virtual world and of the real world. The research used the Design Innovation Method (Kumar V., 2013) which has seven different activity modes for design innovation, namely: Sense Intent, Know Context, Know People, Frame Insights, Explore Concepts, Frame Solutions, and Realize Offerings. The result of the research was a virtual library prototype at the SBY*Ani Museum and Gallery which is an effort to develop the architecture of the library space in the virtual world combined with architecture in the real world. The development was carried out to accommodate space needs, especially a pleasant space experience and user friendly space that provide books and collections, and to design other spaces that can be built in the virtual world, with attractive interior designs, user friendly products, safe, comfortable, and flexible for readers/borrowers. By this research process which was using the Design Innovation Method, at least three prototypes were found, namely D0, D1, and D2. All three have been tested and are being evaluated to establish the findings of the research. This research has limitations in terms of funding and research work time, in which researchers must combine the research work schedule with the work schedule for the SBY*Ani Museum and Gallery construction project, as well as the situation and conditions for the application of restrictions on community activities due to the Covid-19 pandemic. The research value was unique in terms of the research methods and findings, originality, and useful impact that can be felt by the community and owner of the Museum and Gallery SBY*Ani